Null alleles of the X and Y chromosomal amelogenin gene in a Chinese population - Ou, Xueling; Chen, Wenjing; Chen, Hua; Zhao, Fengcang; Zheng, Jianwen; Tong, Dayue; Chen, Yong; Chen, Aiping; Sun, Hongyu (International journal of legal medicine, 2012)
The use of amelogenin locus typing as a gender marker incorporated in short tandem repeat (STR) multiplexes is a common practice in sex typing. Mutations in the X or Y homologue of the amelogenin gene can be misleading and result in serious mistakes in forensic applications and prenatal diagnosis. In these present studies, the amelogenin gene of 8,087 unrelated male individuals from Chinese Han population was genotyped with Powerplex ® 16 system. The samples that showed discordant results were taken for frequency calculation and further validated by re-amplification with different primer sets, Y-STR typing, and sequencing. Our results describe six amelogenin X-allele ( AMELX ) or amelogenin Y-allele ( AMELY ) null cases in these studied subjects with an overall prevalence of 0.074%. Further validation revealed point mutations in the amelogenin-priming sites associated with AMELX nulls (three cases, 0.037%) and deletions on the Y chromosome encompassing the AMELY and other Y-STR loci with three AMELY nulls (0.037%). These mutations and failure of the amplification of the AMELX and AMELY alleles have not been reported for the Chinese population. These and previous findings suggest that mutations in the amelogenin gene may result in amplification failure of the AMELX or AMELY allele, and an additional gender test for unambiguous sex determination may be needed.